A Pengaruh Karakteristik Individu, Kualitas Kehidupan Kerja Dan Fasilitas Kerja Terhadap Kinerja Karyawan PT. Serbuk Jaya Abadi - Lailatur Rizki, Via; Luthfiyah, Siti Nur Azizatul (Jurnal Istiqro, 2025)
This study aims to determine the effect of individual characteristics, quality of work life, and work facilities on employee performance of PT Serbuk Jaya Abadi in Lumajang City. Data collection was obtained through distributing questionnaires and interviews to respondents with the slovin sampling method, which 60 employees. The results of the data were processed using the analytical tool multiple linear regression. With the results of individual characteristics do not have a significant effect on employee performance. On the contrary, the quality of work life and work facilities have an effect on employee performance.